2021
DOI: 10.1002/batt.202100243
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheets Derived through Dissolution‐Recrystallization of TiB2 as Efficient Anode for Sodium‐Ion Batteries

Abstract: Metal borides when subjected to dissolution and recrystallization exhibit a tendency to grow preferentially in lateral dimensions and form nanosheets. Such derived nanosheets exhibit unusual properties that can potentially be used in energy conversion and storage applications. Here we report boride-based nanosheets derived from titanium diboride through a scalable one-pot chemical approach as a sodium-ion battery anode material. The half-cell with TiB 2 -derived nanosheets (TiB 2 -NS) as anode delivers an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In a recent study, Suriyakumar and co-workers have demonstrated TiB 2 nanosheets as a sodium-ion battery anode material for battery applications. 64 Their results revealed that the TiB 2 nanosheet-based anode delivers an initial discharge capacity of 252 mAh/g at 0.1 A/g, as demonstrated in Figure 15A. This study exemplifies the rich potential of TiB 2 nanosheets as an anode material for sodium-ion batteries.…”
Section: Rechargeable Energy Storage Devicesmentioning
confidence: 61%
See 1 more Smart Citation
“…In a recent study, Suriyakumar and co-workers have demonstrated TiB 2 nanosheets as a sodium-ion battery anode material for battery applications. 64 Their results revealed that the TiB 2 nanosheet-based anode delivers an initial discharge capacity of 252 mAh/g at 0.1 A/g, as demonstrated in Figure 15A. This study exemplifies the rich potential of TiB 2 nanosheets as an anode material for sodium-ion batteries.…”
Section: Rechargeable Energy Storage Devicesmentioning
confidence: 61%
“…The studies on layered metal diborides reveal their superior performance in energy storage (LIBs/SIBs, supercapacitors) applications due to improved electrode kinetics, high electroactive surface area, electrolytic stability, and charge transport. , So far, layered metal diborides have been less investigated for energy storage and conversion applications than transition-metal carbides, nitrides, and phosphides. In a recent study, Suriyakumar and co-workers have demonstrated TiB 2 nanosheets as a sodium-ion battery anode material for battery applications . Their results revealed that the TiB 2 nanosheet-based anode delivers an initial discharge capacity of 252 mAh/g at 0.1 A/g, as demonstrated in Figure A.…”
Section: Applications Of Metal-boride-derived 2d Nanostructuresmentioning
confidence: 99%
“…We have previously reported the electrochemical performance of titanium diboride (TiB 2 )based hierarchical nanosheets (THNS) as anode materials for Na-ion batteries (SIBs). 32 However, to the best of our knowledge, no experimental literature is available on any TMD nanostructures as LIB anode.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several theoretical studies on MBenes (2D-Mo 2 B 2 and Fe 2 B 2 ) and monolayer TMDs present their rich candidacy as an active anode for Li- and Na-ion batteries, respectively. We have previously reported the electrochemical performance of titanium diboride (TiB 2 )-based hierarchical nanosheets (THNS) as anode materials for Na-ion batteries (SIBs) . However, to the best of our knowledge, no experimental literature is available on any TMD nanostructures as LIB anode.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a dissolution-recrystallization approach has been reported to prepare TMOs and metal boride electrode materials. [29][30][31][32] The method involves the treatment of TMOs and metal boride bulk raw materials with solutions of alkali and alkaline earth metal salt solution. The bulk raw materials, when subjected to dissolution and recrystallization in the aqueous solution in the presence of alkali metal salts, alkaline earth metal salts, or even conductive polymers, 33 tend to grow preferentially in lateral dimensions.…”
Section: Introductionmentioning
confidence: 99%